The great plan - Wheeler, Chase (New York : Grosset & Dunlap, 2008)
Speed Racer is ready for the Sword Mountain Race, but instead of focusing on his racing, Speed Racer needs to protect the plans for his car, the Mach 5, which other competitors are trying to steal.
3-6
3-6
Keywords: Automobile drivers -- Juvenile fiction; Automobile racing -- Juvenile fiction; Automobile drivers -- Fiction; Automobile racing -- Fiction; Automobile drivers -- Fiction; Automobile racing -- Fiction